Thrombocytopenia and Malaria: A coincidental co-existence or a significant association? An Analysis. - Jairajpuri, Zeeba; Rana, Safia; Jaseem, Salamah; Jetley, Sujata (Annals of Pathology and Laboratory Medicine, 2015)
Background: Malaria is a major health problem and a cause of significant morbidity and mortality worldwide especially in the tropics. Anemia, thrombocytopenia, atypical lymphocytosis and infrequently disseminated intravascular coagulation. Leucopenia, leucocytosis, eosinophilia and monocytosis have also been reported. Methods: The aim of the present study was to detect if an haematological index like thrombocytopenia is a significant indicator of malaria and whether its presence increases the probability of malaria in patients suspicious of suffering from this disease. Clinically suspected cases of malaria with febrile illness presenting at Hakeem Abdul Hameed Centenary, Hospital were included in the study and evaluated. Â Results: Among 1248 patients with clinical suspicion of malaria, 230(18%) patients were confirmed by the demonstration of malarial parasite on peripheral blood film mostly in the months of August and September, monsoon season. A male predominance, with a male to female ratio of 2.3:1 was seen. 212 patients out of 230 had accompanying thrombocytopenia. The sensitivity and specificity of this was 92.1% and 88.2% respectively with a disease prevalence of 19%. The positive and negative predictive values were 63.8% and 98.1%with a positive likelihood ratio (LR+) of 7.82 and negative likelihood ratio(LR-) of 0.09. Conclusions:Â  The malaria-endemic regions of the world are mostly developing countries with limited resources and trained health personnel. The hematological aspects may be used in addition to the clinical assessment, to heighten the suspicion of this disease. Thrombocytopenia is associated with both P. falciparum and P. vivaxinfections. Significant association between malaria and thrombocytopenia has been demonstrated in our study and we suggest malaria should be a consideration in all patients with fever and low platelet counts.